The origin of the Mycoplasma mycoides cluster coincides with domestication of ruminants - Fischer, A.; Shapiro, Barry I.; Muriuki, C.; Heller, M.; Schnee, C.; Bongcam-Rudloff, E.; Frey, J.; Jores, Joerg (Public Library of Science, 2012)
The ‘Mycoplasma mycoides cluster’ comprises the ruminant pathogens Mycoplasma mycoides subsp. mycoides the causative agent of contagious bovine pleuropneumonia (CBPP), Mycoplasma capricolum subsp. capripneumoniae the agent of contagious caprine pleuropneumonia (CCPP), Mycoplasma capricolum subsp. capricolum, Mycoplasma leachii and Mycoplasma mycoides subsp. capri. CBPP and CCPP are major livestock diseases and impact the agricultural sector especially in developing countries through reduced food-supply and international trade restrictions. In addition, these diseases are a threat to disease-free countries. We used a multilocus sequence typing (MLST) approach to gain insights into the demographic history of and phylogenetic relationships among the members of the ‘M. mycoides cluster’. We collected partial sequences from seven housekeeping genes representing a total of 3,816 base pairs from 118 strains within this cluster, and five strains isolated from wild Caprinae. Strikingly, the origin of the ‘M. mycoides cluster’ dates to about 10,000 years ago, suggesting that the establishment and spread of the cluster coincided with livestock domestication. In addition, we show that hybridization and recombination may be important factors in the evolutionary history of the cluster.